Do populations of Festuca pallescens from a rainfall gradient differ in the expression of morpho-physiological traits under drought stress? - López, Aldana Soledad (2023)
In arid environments, stochastic rainfall and high evapotranspiration force plants to optimize water resources. North Patagonia is characterized by a deep rainfall gradient that gives rise to environments with very contrasting water availability. Festuca pallescens is a key native forage species, growing widely in those environments. To explore morphological and physiological traits involved in the response to drought, we exposed plants from populations sampled along the rainfall gradient to different water availability conditions (Well-watered, Water-pulse, Water-drought). We evaluated morphological traits in all populations to assess inter-population variability and physiological traits between selected populations from sub-humid and arid environments to explore possible macro-environmental responses. Populations showed variation in survival after 45 days of drought conditions and differences in the expression of morphological traits. Also, populations from arid environments were less affected than those from humid environments, showing a longer recovery when they received water pulses. Although a population survival pattern related to the rainfall gradient was not evident, populations from arid environments exhibited local adaptation to their home environments, taking better advantage of water pulses. These results provide information about the response of a non-model species to environments with contrasting water availability and possibly, to changing rain patterns in arid environments under climate change. Data Availability Statement: The data that support the findings of this study are available from the corresponding author upon reasonable request.